Asahel Curtis setting up camera on tripod along the Skagway Canyon, White Pass Trail, 1897 - Curtis, Asahel, 1874-1941 (1897)
Caption on image: 46029, Asahel Curtis. Handwritten on verso: 97' Skagway Canyon near White Pass. PH Coll 519.46029 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number